A framework for reforming India's forest biodiversity management regime. (August 2016) - Faizi, S.; Ravichandran, M.
Abstract : India's forest biodiversity management regime is analysed at the policy, legal and institutional levels, from the perspective of the triple objectives of the Convention on Biological Diversity and the principles of the Indian constitution. The forest biodiversity management regime has both structural and functional flaws that render it largely incapable of facing the challenge of increasing biodiversity degradation and deepening poverty among the Adivasis and other forest‐dependent communities. The paper argues for the reform of the forest biodiversity management regime and offers recommendations in regard to most aspects of the regime, with a view of putting the country's conservation enterprise on a course that is effective, sustainable and inclusive, rejecting the report of the High Power Committee (HPC) (also known as the Subramanian Committee), which is premised on easing corporate access to forests.